2009
DOI: 10.1080/00016350802572314
|View full text |Cite
|
Sign up to set email alerts
|

Lengths of the maxillary central incisor, the nasal bone, and the anterior cranial base in different skeletal malocclusions

Abstract: The lengths of the maxillary central incisor and nasal bone, both parameters located in the frontonasal field, are affected in different skeletal malocclusions. The present findings, especially the deviation of the upper incisor length in different skeletal malocclusions, are considered relevant for orthodontic diagnostics and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…It can be hypothesized that the aetiology behind general and local deviation in skull thickness is different. The finding of a local thickening in the frontal bone might be interrelated with the finding of a short nasal bone in this malocclusion group (35). Both areas belong to the frontonasal developmental field (43).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…It can be hypothesized that the aetiology behind general and local deviation in skull thickness is different. The finding of a local thickening in the frontal bone might be interrelated with the finding of a short nasal bone in this malocclusion group (35). Both areas belong to the frontonasal developmental field (43).…”
Section: Discussionmentioning
confidence: 63%
“…These studies also showed that there were different fusion patterns in the different malocclusion groups. Short nasal bone length has recently been found in females with skeletal Class II malocclusion, whereas this was not the case in Class III malocclusion (35). Based on this, it could be hypothesized that there is different skull thickness in skeletal Class II and Class III malocclusions.…”
Section: Introductionmentioning
confidence: 95%
“…2,3 The dental roots of maxillary central incisors in patients with open bite have been reported to be short. 4 Moreover, the loss of normal occlusal function or OC, that is, occlusal hypofunction due to tooth loss or in malocclusions such as open bite, leads to root resorption during tooth movement. 5 Thus, open-bite malocclusion and loss of OC play an important role in dental root morphology, although the details remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 However, few studies have evaluated the original dental root length in patients with open bite. 4 The purpose of this study was to examine the R/C ratio and dental root length of all teeth in patients with open bite and its relationships to OC and the Mp angle.…”
Section: Introductionmentioning
confidence: 99%
“…That indicates a risk of a short length of roots due to the developmental anomaly of the anteriors. [4][5][6] Frequent occurrence of morphological features with Class-III malocclusion is long faces and high mandibular plane angle. This trait is attributed to the weak orofacial musculature associated with Class-III malocclusion.…”
Section: Introductionmentioning
confidence: 99%